Cordia trichotoma development in function of the fertilization in silvipastoral system in Southwest region of Paraná-Brazil - Antonelli, Priscyla Vanessa; Brun, Eleandro José; Santos, Marcielli Aparecida Borges dos; Sartor, Laercio Ricardo; Brun, Flávia Gizele Konig (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
This study aimed mainly to analyze the initial development of the louro-pardo (Cordia trichotoma (Vell.) Arrab. ex Steud.), planted at different levels of fertilization in silvopastoral system. Therefore, was made a louro-pardo consortium with grass Panicum maximum cv. aruana at the Universidade Tecnologica Federal do Paraná - Campus Dois Vizinhos. Were allocated 4 double lines in the range of 10 m with spacing of 2.0 m x 1.5 m these lines. The soil was prepared with a scarifier up until a depth of 30 cm. In the planting, jointly the seedlings were added 250 ml/plant of a hydrogel solution. In order to assess the importance of NPK fertilization on the system, this was tested at four different levels (treatments): T1 (without fertilization), T2 (recommended), T3 (twice the recommended) and T4 (triple the recommended). To evaluate the study, plant height measurements were made, stem diameter and two equidistant crown diameters, also were made qualitative evaluations of vigor, according health parameters, occurrence of pests or diseases, growth, overall visual appearance of the leaves and stem, nutrition and water stress. Data were statistically analyzed by software Assistat v. 7.6 Beta. The results showed a mean relative growth of 374.2% for the stem diameter, 278.3% for height and 1351.1% for crown area in the 10 months evaluated. The plant vigor was not influenced by the fertilizer levels, as independent of the tested treatment, there was significant reduction in the quality of seedlings due to the occurrence of bacteria and the coincidence with the winter period, because it is a deciduous plant. According to the study, can be recommended the dose of 192 g plant-1 (T4) of NPK with the tested formulation to louro-pardo.